Differential Contributions of Parental Warmth and Mindfulness to Child Executive Function and Pediatric Type 1 Diabetes Management. Issue 9 (16th December 2022) - Yeo, Anna J.; Ledsham, Victoria; Halpern, Leslie F.; Lin, Betty; Riddick, Linda; Sima, Daniela; Wohlfahrt, Kristine M.; Jones, Nancy
ABSTRACT: Objective: Positive parenting (e.g., parental warmth, mindful parenting) has been posited to promote effective pediatric type 1 diabetes mellitus (T1DM) management. This promotive effect may partly be conferred by fostering child self-regulatory development, such as executive function (EF). However, no research has examined whether better child EF serves as a mechanism underlying associations between positive parenting and child blood glucose levels (HbA1c). Moreover, it is unclear whether mindful parenting offers a unique benefit beyond that of parental warmth—a key pillar of effective parental involvement in T1DM management. Methods: Primary caregivers of children with T1DM (N = 101; Mage = 12.02) reported on parenting behaviors and child EF. Children's medical information was obtained through chart review. Path analysis was used to examine direct and indirect relations in the cross-sectional data. Results: The path analysis indicated that only parental warmth, not mindful parenting, was significantly associated with lower HbA1c. Both parental warmth and mindful parenting were significantly related to better child EF, but child EF did not mediate the associations between parenting and HbA1c. Conclusion: Parental warmth may constitute a key parenting behavior promoting effective pediatric T1DM management. Enhancing parental warmth may be an important target of interventions aiming to improve HbA1c. Although child EF was unrelated to HbA1c in this sample, given positive associations between parental warmth and mindfulness and child EF, longitudinal research is warranted to examine whether these positive parenting behaviors may confer long-term benefits for T1DM self-management through improved EF.